Outcome of Endoscopy-Assisted Microscopic Extended Transsphenoidal Surgery for Suprasellar Adult Craniopharyngiomas - Ikeda, Hidetoshi (Frontiers in Endocrinology, 2012)
Objectives. Craniopharyngiomas are difficult to treat. The extended transsphenoidal approach has recently been described in several small series. We describe the usefulness of microscopy-assisted angled endoscopy for visualizing vital structures such as tumor attachment or tumor invasion to the pituitary stalk to achieve confident radical tumor removal. Design and Participants. Between 2006 and 2010, 15 patients underwent the microscopy-assisted extended transsphenoidal approach for resection of entirely suprasellar craniopharyngiomas. 14 patients had the transinfundibular type, and one had the transinfundibular type with the extension to third ventricle. We observed color change within the pituitary stalk by endoscopy. The pituitary stalk was cut intentionally in ten patients, because of suspected tumor invasion surrounding the stalk. Main Outcome Measures and Results. Total removal was accomplished in nine patients. Pathological specimens from the pituitary stalk showed tumor invasion spreading over the surface of the pituitary stalk, shown by a discolored pituitary stalk, and this was　essential for confident radical tumor removal. Even after stalk resection, postoperative DI was minimal when a bright signal on T1 in the posterior lobe was not confirmed on preoperative magnetic resonance imaging. Conclusion. Confident radical tumor removal is possible with the introduction of the endoscopy-assisted microscopic extended transsphenoidal approach.